The Deciding Factor Is The Timeliness Of Corporate Internet Reporting On Manufacturing Companies Registered In Bei - V.Wiratna Sujarweni; Lila Retnani Utami ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2016)
This remarkable technological development become a part of helping human’s works at this time. Technology will be used by humans to make ther activity become more effective and efficient. Internet proofs the existence of the rapid technological development, internet become one of the new alternative for a company to provide the information of their company both financially or non-financially. This research aims to analyze the defining factor of Corporate Internet Reporting’s timeliness. The research’s population is all registered manufacture company in Indonesia Stock Exchange. The sample using purposive sampling method. Data collecting method is using documentation method. Hypothesis testing using logistic regression analysis. The results of this research is that the defining factor from Corporate Internet Reporting’s timeliness variable company, profitability, laverage, liquidity, issue of shares measurement.